Lean-Based Process Redesign to Optimize Internal Material Flow between Warehouse and Assembly: A Case Study in a Manufacturing Facility - Şengül Coşkun (Department Industrial Engineering, University of Muhammadiyah Malang, 2026)
Although inventory management is essential for competitiveness, limited research exists on process-based redesign of internal material flow between warehouse and assembly units in manufacturing operations. This study presented a new approach to material flow between warehouses and assembly shops in manufacturing, examining inefficient resource utilization caused by prolonged internal logistics processes, including incorrect deliveries, data entry errors, and demand irregularities. The aim of the study was to identify and eliminate all factors that can prevent the material flow between the warehouse and assembly units from being completed within the specified time. This analysis identified bottlenecks and inefficiencies that negatively affected productivity. The improvements reduced handling times from warehouse to assembly by 10% and standardized the process. Manual errors were minimized, traceability of material flows was improved, and flexibility and responsiveness of business processes were increased. These results offered practical insights for manufacturing managers seeking to redesign internal logistics processes using lean tools. The study also contributed to the limited empirical literature on intra-facility material flow optimization. Managers could adopt the proposed process design to increase responsiveness and reduce operational errors in similar manufacturing environments. Future research was suggested to explore the integration of this approach into other logistics activities.